Updated long-term survival outcomes for patients with locally advanced gastric cancer having pathological complete response after neoadjuvant therapy at China National Cancer Center, 2004–2023 - Sun, Chongyuan; Wang, Tongbo; Zhang, Xiaojie; Zhao, Lulu; Niu, Penghui; Wang, Wanqing; Luan, Xiaoyi; Han, Xue; Chen, Yingtai; Zhao, Dongbing (Frontiers in Oncology, 2025)
BackgroundNeoadjuvant chemotherapy increases the probability of achieving negative margins and may even lead to pathological complete response (pCR) in locally advanced gastric cancer (LAGC). The incorporation of neoadjuvant immunotherapy is promising in further enhancing the pCR rate. However, long-term survival outcomes and factors affecting the prognosis of pCR patients have not been fully elucidated.Patients and methodsWe conducted a retrospective analysis of all patients who achieved pCR between January 2004 and June 2023. Cox regression models were used to identify clinicopathological predictors of overall survival (OS) and disease-free survival (DFS). Survival curves were plotted using the Kaplan–Meier method and compared using the log-rank test.ResultsAfter screening, 112 patients were included in the study, with a median follow-up time of 42 (range: 2-117) months and a pCR rate of 7.4%. The 3- and 5-year OS rates were 90.2% and 83.3%, respectively, while the 3- and 5-year DFS rates were 86.8% and 82.0%, respectively. Within the multivariate Cox model, neoadjuvant chemotherapy was a prognostic factor for improved OS and DFS. There was no statistically significant disparity in OS and DFS between patients who received postoperative adjuvant therapy and those who did not. Moreover, the combination of neoadjuvant immunotherapy with chemotherapy, as compared to neoadjuvant chemotherapy alone, substantially increased the pCR rate (p <0.001).ConclusionsPatients with LAGC who achieved pCR demonstrated favorable long-term survival outcomes, with no additional survival benefits conferred by adjuvant therapy. Although neoadjuvant immunotherapy increased the pCR rate, its impact on the prognosis of pCR patients requires further investigation.